2018
DOI: 10.1007/s10815-018-1236-z
|View full text |Cite
|
Sign up to set email alerts
|

Associations of semen quality with non-essential heavy metals in blood and seminal fluid: data from the Environment and Male Infertility (EMI) study in Lebanon

Abstract: Environmental exposures to Pb, Cd, Ba, and U appear to adversely influence sperm development in men. In non-occupationally exposed men, measurements of heavy metals in the seminal fluid may be more predictive of below-reference sperm quality parameters than in blood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
49
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 55 publications
0
49
1
4
Order By: Relevance
“…Mercury has a negative role in fertility, both in men and women . In women, infertility is influenced by an imbalance of the female hormonal system due to Hg exposure.…”
Section: Mercury Exposure and Fertility: General Aspectsmentioning
confidence: 99%
See 3 more Smart Citations
“…Mercury has a negative role in fertility, both in men and women . In women, infertility is influenced by an imbalance of the female hormonal system due to Hg exposure.…”
Section: Mercury Exposure and Fertility: General Aspectsmentioning
confidence: 99%
“…The progesterone/oestrogen ratio changes in favour of oestrogen growth, which inhibits the release of LH‐luteinizing hormone. Thus, Hg may induce feminine infertility by increasing the prolactin secretion—analogous to the dopamine effect at the pituitary and midbrain level, with negative effects on galactopoiesis and female genitalia . Xenobiotics such as Hg, xenoestrogens, and synthetic oestrogens are endocrine disruptors present in most commercial foods, plastic products, tap water, plastic water glass, cosmetics, cleaning products, clothes detergents, paints, pesticides and insecticides .…”
Section: Mercury Exposure and Fertility: General Aspectsmentioning
confidence: 99%
See 2 more Smart Citations
“…A study also found that follicle-stimulating hormone deficiency could affect male fertility 30 . Several studies focused on environmental chemical substances, including perfluoroalkyl compounds, Pb, Cd, Ba, and U, have demonstrated that these substances may adversely affect seminal quality [31][32][33] . To summarize, seminal plasma functions not only as a medium to carry, protect, and nourish sperm after ejaculation up to fertilization, but also modulates sperm functions 34 .…”
mentioning
confidence: 99%